Optical coherence tomography angiography discerns preclinical diabetic retinopathy in eyes of patients with type 2 diabetes without clinical diabetic retinopathy - Cao, Dan; Yang, Dawei; Huang, Zhongning; Zeng, Yunkao; Wang, Jun; Hu, Yunyan; Zhang, Liang (Acta diabetologica, 2018)
Aims To investigate changes in retinal vascular plexuses and choriocapillaris in patients with type 2 diabetes mellitus (DM2) without diabetic retinopathy (DR) and healthy controls using optical coherence tomography angiography (OCTA). Methods A total of 71 DM2 and 67 healthy control subjects were included. All subjects underwent OCTA examination (RTVue-XR Avanti; Optovue, Fremont, CA, USA). Average vessel density in superficial capillary plexus (SCP), deep capillary plexus (DCP) and choriocapillaris, parafoveal vessel density in SCP and DCP, FAZ area (mm 2 ) in SCP, microaneurysms and capillary nonperfusion were taken into analysis. Results Parafoveal vessel density in both SCP and DCP decreased in the eyes without clinical DR compared to normal controls ( p < 0.001). Diabetic patients with no signs of DR also had a significant reduction in average vessel density of SCP, DCP and choriocapillaris ( p < 0.001, p < 0.001 and p = 0.006, respectively). No significant difference was found in FAZ area of SCP between DM2 eyes and healthy controls ( p = 0.253). The average vessel density of SCP and DCP is not correlated with HbA1c or serum creatinine in DM2 patients. Microaneurysms seen in OCTA but not in fundus examination were found in 8 out of the 71 (11.3%) diabetic eyes, and capillary nonperfusion was noted in 18 of 71 diabetic eyes. Conclusions We demonstrated that OCTA can identify preclinical DR before the manifestation of clinically apparent retinopathy in diabetic eyes. DM2 patients without DR have SCP, DCP and choriocapillaris impairment. Our results suggested that OCTA might be a promising tool for regular screening of diabetic eyes for DR.